Understanding experiential value delivery: The important role of salespeople’s orientation - Gilang Puspita Rini; Rhealin Hening Karatri; Annsiya Lutfi Septanti; Evana Andriani; Norhazlin Binti Mohamed Ali (Universitas Ahmad Dahlan, 2026)
Customer orientation is widely regarded as a key driver of firm performance. This study examines how customer orientation, selling creativity, and proactive service behavior affect sales performance by delivering experiential value. This was examined by embedding customer experience within the experiential value that salespeople deliver in the cosmetics industry in developing countries. While traditional frameworks focus on passive customer experience management or static service quality, experiential value delivered introduces a novel behavioral construct. It captures the salesperson's active role in co-creating and operationalizing value in real-time interactions, shifting the focus from organizational systems to dyadic frontline behaviors. Data were collected from 210 salespeople in the Indonesian cosmetics industry and analyzed using a structural equation model in AMOS 25. The results showed that cosmetics companies that adopted a customer-oriented approach and delivered experiential value enhanced sales performance. Experiential value delivery also mediated the relationship between customer orientation and sales performance. Grounded in the service-dominant logic framework, experiential value delivered serves as a crucial behavioral catalyst for value co-creation. This study contributes to the service-dominant logic literature by providing a concrete behavioral mechanism that links a firm's strategic customer orientation to frontline sales performance.